The Use of a Relay Race Game to Increase Grade V Students’ Motivation in Learning English in an Elementary School in Karawaci - Erinca Simarmata; Siane Indriani (Universitas Pelita Harapan, 2016)
Through an observation done of fifth graders in an elementary school at Karawaci, Tangerang, it was found that the students did not show much motivation in learning English in the classroom. They did not show interest in doing their tasks and they did not show respect while doing activities with their friends during lesson times. Motivation is important in energizing, directing, and sustaining (good) behavior of students during the learning process in the classroom. Therefore, the researcher decided to use a relay race game to solve the problem. It was expected that through the relay race game, the students’ motivation would be increased and how the steps of the game would increase the students’ motivation in learning English. The method used was Classroom Action Research and data was collected by using several instruments, such as an observation checklist done by the mentor and researcher’s partner, questionnaires done by the students, and reflective journals done by the researcher. After conducting the research, the results showed that the motivation of students learning English increased using a relay race game and the steps of the game must be done consistently to make it effective.BAHASA INDONESIA ABSTRAK: Selama masa pengamatan yang dilakukan di kelas V di sebuah sekolah dasar di Tangerang, ditemukan bahwa siswa tidak menunjukkan ketertarikan terhadap pelajaran dan usaha dalam mengerjakan tugas- tugas di kelas. Siswa tidak menunjukkan motivasi yang besar dalam pembelajaran Bahasa Inggris di kelas. Metode yang diadakan oleh peneliti adalah Penelitian Tindakan Kelas (PTK). Tujuan penelitian adalah untuk mengetahui bagaimana permainan Relay Race dapat meningkatkan motivasi belajar siswa dalam belajar Bahasa Inggris dan bagaimana prosedur permainan Relay Race diterapkan di pembelajaran tersebut. Instrumen yang digunakan adalah observasi checklist oleh mentor dan rekan peneliti, kuisioner oleh siswa, dan jurnal refleksi oleh peneliti. Setelah mengadakan penelitian ini, hasil yang diperoleh adalah bahwa motivasi siswa dalam belajar Bahasa Inggris dapat meningkat menggunakan permainan Relay Race.